Growth, Survival and Fecundity in Ornamental Fish, Betta splendens (Regan) as a Function of Stocking Density R. - R., James; K., Sampath (Fishery Technology, 2025)
Effects of stocking density (10,25,50,100 and 150 fish/501 ofwater) on growth, survival and fecundity were studied in Siamese fighting fish, Betta splendens. An increase in stocking density reduced the growth, survival and fecundity in B. splendens. A significant (P < 0.05) negative correlatibyi was obtained between density and feeding parameters or gonad weight or fecundity in B. splendens. Animals reared in higher densities elicited poor gonad development and it severely affected egg production and hatching. Accumulation of more ammonia and carbon dioxide and oxygen depletion with increase in stocking density could have reduced the feed consumption and growth which in turn affected the gonad development and fecundity in female B. splendens. However, fish reared in 10 and 25D groups could withstand ammonia stress of 1.01 mg l1 without any ill effect on survival, growth, gonad development and fecundity. Fish reared in 10 D group displayed better rates of feeding and growth at early rearing period than those in 25D group. However, fish reared in 25D group showed significantly higher growth rate (t=2.71; P<0.05) and growth efficiency (t=2.67; P<0.05) than fish reared in 10D group and also in higher density groups when fish attained sexual maturity on day 42. Although fish reared in 10D laid more eggs per female B. splendens than 25D group, the total number of egg production was higher in 25D than 10D group. The percentage of egg hatchability between 10D and 25D groups did not show significant (P<0.05) difference between them. Fish reared in 25D group exhibited 100% survival like 10 D group. Based on the survival, growth rate, total number of egg production, and egg hatching rate, fish reared in 25D group is economically better than 10 D or higher than 25D groups and hence 25 fish 50 11 water is considered as optimum density.